Cultura tributaria y gestión del impuesto predial en los contribuyentes de la Municipalidad Provincial de Requena, año 2024 - Pacaya Machoa, Kari Lizbet (2024)
The objective of this research was to determine the relationship between tax culture and property tax management among taxpayers of the Provincial Municipality of Requena, year 2024. The research methodology used comprised a quantitative approach, non-experimental design, correlational level and basic type, while a questionnaire was applied to a sample composed of 40 actors among taxpayers of the Provincial Municipality of Requena, as well as independent professionals on tax culture and property tax. The main results showed that most of the respondents agreed on the relevance of creating a tax culture among taxpayers of the Requena Provincial Municipality, considering dimensions such as tax education and tax awareness, as a means to improve property tax management in the jurisdiction, taking into account dimensions such as principles and elements of the tax. The main conclusion was to have determined that there is a significant relationship between tax culture and property tax management among taxpayers of the Provincial Municipality of Requena, year 2024. This conclusion was supported by the correlation index (Spearman) reached for the general hypothesis, which was 0.988.